2004
DOI: 10.4269/ajtmh.2004.71.387
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Water-Related Risk Factors for Buruli Ulcer: A Case-Control Study in Ghana

Abstract: To assess water-related risk factors of Buruli ulcer, a case-control study of 102 patients (51 cases and 51 controls) was undertaken by matching age group, sex, and bacille Calmette-Guerin (BCG) vaccination history in Ghana. The factors used here for matching have previously been implicated as factors of Buruli ulcer, an emerging infectious disease. This is the first study to delineate a set of previously suspected, water-related risk factors, in a case-control study matching for age group, sex, and BCG vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
97
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 26 publications
4
97
0
1
Order By: Relevance
“…Although several water-related risk factors have been recognized, none has been consistently reported, making it diffi cult to identify specifi c water-related risk activities (6)(7)(8). Most studies suggest that infection occurs through inoculation of M. ulcerans into skin lesions or insect bites (2,4,9-11).…”
mentioning
confidence: 99%
“…Although several water-related risk factors have been recognized, none has been consistently reported, making it diffi cult to identify specifi c water-related risk activities (6)(7)(8). Most studies suggest that infection occurs through inoculation of M. ulcerans into skin lesions or insect bites (2,4,9-11).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that populations that use unprotected sources of water for domestic purposes have prevalence rates of BU higher than those who use protected sources (1,21,30,54). The preferable habitat of M. ulcerans is probably unprotected waters, since the presumed reservoir and/or vector(s) of M. ulcerans probably occurs more frequently in unprotected waters (39).…”
Section: Discussionmentioning
confidence: 99%
“…La dĂ©monstration, chez des souris infectĂ©es par M. ulcerans, de l'efficacitĂ© de l'association de deux antibiotiques, la rifampicine et l'amikacine, a contribuĂ© Ă  la rĂ©alisation de deux Ă©tudes thĂ©rapeutiques pilotes qui ont confirmĂ© l'intĂ©rĂȘt de cette antibiothĂ©-rapie puisque la moitiĂ© des patients a Ă©tĂ© guĂ©rie sans avoir recours Ă  la chirurgie [2]. À l'heure actuelle, il n'existe pas de vaccin spĂ©cifique dirigĂ© contre M. ulcerans et l'efficacitĂ© de la vaccination BCG est, pour les formes cutanĂ©es, fort controversĂ©e [3,4]. [5].…”
Section: En Conclusionunclassified